Neighbourhood socioeconomic disadvantage from childhood to midlife and carotid atherosclerosis. - Raitakari, Olli; Pentti, Jaana; Koskinen, Juhani S.; Mykkänen, Juha; Rovio, Suvi; Pahkala, Katja; Juonala Markus; Lehtimäki, Terho; Kähönen, Mika; Kawachi, Ichiro; Kivimäki, Mika; Viikari, Jorma; et al. (Elsevier, 2026)
Background
Neighbourhood socioeconomic disadvantage correlates with cardiovascular disease risk. However, its relationship with subclinical atherosclerosis from childhood to midlife is not well-defined. We examined whether cumulative neighbourhood disadvantage is associated with carotid artery plaques, a measure of subclinical atherosclerosis.
Methods
We analysed data from 1998 participants in the Cardiovascular Risk in Young Finns Study, a cohort followed from childhood (mean age 10.7 years in 1980) to adulthood (mean age 48.6 years in 2018–2020). Neighbourhood disadvantage was derived from national grid-based socioeconomic data and computed cumulatively across the life course. The number of carotid artery plaques (mean plaque count) was assessed by standardized ultrasound imaging. Multivariable Poisson regression models were used to evaluate the associations. Mediation analyses were used to assessed the role of ideal cardiovascular health (CVH) metrics.
Results
Higher cumulative neighbourhood disadvantage from childhood to mid-adulthood was associated with a 1.24-fold increase in mean plaque count for every 1 standard deviation increase in cumulative disadvantage. This relationship persisted after controlling for parental carotid artery plaques, polygenic coronary artery disease risk score, and Framingham risk score. The association was partially explained by ideal CVH metrics, particularly smoking and blood pressure, which collectively accounted for almost half of the association.
Conclusions
Long-term exposure to neighbourhood socioeconomic disadvantage beginning in childhood is associated with subclinical atherosclerosis in midlife, independently of achieved socioeconomic position. These findings highlight the importance of cumulative socioeconomic environments across the life course and suggest that behavioural risk factors may partly explain observed neighbourhood-level associations with atherosclerosis.